Penguatan identitas tempat melalui pemetaan budaya, Studi kasus: Kampung Madura Pendalungan di Baran Buring, Malang - Ema Yunita Titisari; Lisa Dwi Wulandari; Yusfan Adeputera Yusran (ARTEKS : Jurnal Teknik Arsitektur, 2023)
The place identity needs to be resurfaced visual-architecturally through place-making and community engagement. From participatory identification of tangible and intangible cultural assets, cultural mapping can increase awareness of cultural assets and a sense of belonging, facilitate network development and collaboration, and prepare village development programs according to local potential. This study aims to compile the potential and resources of Kampung Baran in a participatory manner, and then present it as significant cultural character data in shaping the identity of the place. The research was conducted qualitatively through asset mapping and community identity mapping. Asset mapping is related to the physical resources, while community identity mapping identifies intangible resources. Physical data recording is done through field observation. The on-site data mapping is triangulated through focus group discussions and in-community conversation to identify the intangible resources. Furthermore, the data were categorised, and the relations were analysed to compile the cultural mapping. The results showed that the unity between architectural elements (recontextualization of Omah Gejug), communal space according to the taneyan pattern of Kampung Baran, typical plants, local culinary, traditional arts and language, as well as socio-cultural systems and structures can be visualized to support the revitalization of place identity.